Mobile Communication and Urban/Rural Flows in a South African Marginalised Community. (June 2023) - Dalvit, Lorenzo
This article draws on Castells' concept of space of flows to explore the role of mobile communication in mediating the flows of ideas, people and resources concerning Dwesa, a rural community in South Africa. While it is the site of an ICT-for-development project fifteen years in the making, Dwesa is representative of many contemporary South African rural realities in terms of lack of infrastructure, endemic poverty and urban migration. Mobile network coverage is almost universal, sustaining a bidirectional flow of people, resources and information between Dwesa and urban areas such as Cape Town. A critical review of the substantial body of research conducted in the area, as well as thematic analysis of social media texts and semi-structured interviews with community members, reveal that mobile phones play an important and nuanced role in arranging physical or virtual rendezvous, facilitating transfers of monetary and other resources, and enabling timeless communication and exchange of information across distance.